Políticas anticíclicas na indústria automobilística: Uma análise de cointegraç\~ao dos impactos da reduç\~ao do IPI sobre as vendas de veículos - Gustavo Varela Alvarenga; Patrick Franco Alves; Carolina Fernandes dos Santos; Fernanda de Negri; Luiz Ricardo Cavalcante; Maria Cristina Passos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The aim of this paper is to analyze the impacts of the reduction of the Brazilian Tax on Industrialized Products (IPI) on the local sales of vehicles during the period between January and November of 2009. In order to evaluate these impacts, sales have been modeled as a function of price, income and credit for the acquisition of vehicles. The econometric model takes into account the existence of short run and long run relationships among the variables. The results obtained for the long run elasticities of transmission as well as for their short run adjustment speeds reinforce the perception that the reduction of the IPI was particularly relevant to the recovery of the vehicle sales in Brazil in the period after the international financial crisis. The results showed that 20.7% of the vehicle sales during the period can be associated to the reduction of the IPI. An increment in the credit for the acquisition of vehicles could have showed a not negligible effect on the vehicle sales especially in the absence of other countercyclical measures in 2009.
Keywords: H3; 330; Kraftfahrzeughandel; Industrieprodukt; Steuer; Steuerwirkung; Brasilien